Biochar effects on the seedling quality of Quercus serrata and Prunus sargentii in a containerized production system. Issue 3 (3rd July 2018) - Aung, Aung; Han, Si Ho; Youn, Woo Bin; Meng, Loth; Cho, Min Seok; Park, Byung Bae
Abstract: Biochars are used to improve soil quality and crop productivity as well as to increase carbon sequestration in soil. However, it is important to identify the characteristics of biochar prior to its application because of the positive and negative effects on soil and crop productivity. The purpose of this study was to investigate the effects of charcoals on the growth and seedling quality of Quercus serrata and Prunus sargentii in a containerized seedling production system. Two of the charcoals used in our research were from oak tree; one produced at 1200 °C and the other at 700 ∼ 800 °C, and a bamboo charcoal produced at about 800 °C. Three charcoals were mixed with artificial soil (peat moss, perlite, and vermiculite with a ratio of 1:1:1 (v/v/v)), and applied commercial fertilizer at two concentrations; 0.5 and 1.0 g L −1 . Growth parameters, such as height, root collar diameter, and dry weight, were decreased in charcoal treatments compared to control. However, charcoal treatments significantly increased the quality index of seedlings by 8.3% in Q. serrata and by 19.9% in P. sargentii . Our results suggested that charcoal can be applied to improve seedling quality in the containerized Q. serrata and P. sargentii seedling production system.